ADEQUATE CHARACTERISTICS OF ENGLISH AND UZBEK PROVERBS WITH ZOOCOMPONENTS (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2024)
adequate (lat. adaeguatus - equal, suitable, exactly, similar) - from the theory of knowledge means the properties and relations of the various phenomena that correspond to their objective content, can be identified and adapted. This article is devoted to the adequate properties of objects. Words with zoocomponents in English and Uzbek languages ​​were analyzed.